PEMBERDAYAAN MEDITOR LOKAL SEBAGAI PROBLEM SOLVER DALAM SENGKETA PERCERAIAN MASYARAKAT MUSLIM DESA KALISAT PASURUAN - Salam, Nor; Nurcholis, Moch.; Junaidin, Junaidin (LPPM Institut Agama Islam Bani Fattah Jombang, 2023)
The activity with the theme “Empowering Local Meditors as Problem Solvers in Divorce Disputes in the Muslim Community of Kalisat Pasuruan Village” was motivated by the presence of a Supreme Court Regulation (PERMA) with one of its “doctrines” namely the validity of mediators who are entitled to mediate in divorce disputes are mediators consisting of judges or non-judge but certified mediators. This has implications for the